A Study on Neutrophil Lymphocyte Ratio in Covid 19 Patients in Tertiary Care Centre (International Journal of Physiology, 2021)
Introduction: COVID-19 pandemic is spread by droplet infectionwith symptoms of fever, cough,diarrhea,dyspnea, fatigue, myalgia, headache, anosmia and ageusia. Morbidity and mortality is higher amongelderly and in patients with comorbidities especially Diabetes Mellitus(DM). Biomarkers of inflammationare potential predictors for prognosis in covid patients.Aim: To analyze the association of NLR in covid 19 patients with symptoms and diabetic status Objective:1. To studyNLR in covid 19 patients with and without symptoms2. To study the association of NLR between diabetic and non-diabetic covid 19 patients.3. To study the association between symptomatology and NLR in diabeticcovid 19 patients.Methodology: 3000 RT-PCR confirmed Covid 19 patients who attended triage op were included afterEthicscommittee approval.Patients were grouped as patients with and without symptoms and patients with andwithout DM.The diabetic Covid patients were also analyzed based on the symptoms. Blood samplesonreporting were used for analysis of NLR andparameters analyzed using SPSS23.0 version.Result: There is no statistically significant difference in NLR among Covid symptomatic and asymptomaticpatients. But NLR is markedly raised in covid symptomatic patients with diabetes mellitus.